PUBLICATION ACTIVITY OF MEMBERS OF DISSERTATION COUNCILS AT UNIVERSITIES IN RUSSIA - Valery A. Gurtov; Lyudmila V. Shchegoleva (Moscow Polytechnic University, 2016)
The article presents the results of analysis of publication activity of dissertation councils' members as a whole and separately for members of dissertation councils at universities. The analysis is based on the monitoring data of scientific activity of members of dissertation councils, held in 2013. The results showed significant differences in the values of indicators for different areas of science. This difference supposes a variety of approaches to the assessment and promotion of the publication activity of scientists in different fields of science.